High power and compact switchable bismuth based multiwavelength fiber laser - Ahmad, Harith; Zulkifli, Mohd Zamani; K, Thambiratnam; Latif, S.F.; Harun, Sulaiman Wadi (IOP Publishing, 2009)
A compact switchable multiwavelength fibre laser (SWFL) is proposed and demonstrated using a bismuth based erbium doped fibre amplifier (Bi-EDFA) and a Sagnac loop mirror (SLM) in a ring cavity. The proposed compact SWFL can generate up to 6 switchable wavelengths with an average peak power of 11 dBm and also shows good stability over time with a high side mode signal ratio (SMSR) of 40 dB that negates minor fluctuations in the laser output. The Bi-EDF based gain medium gives the SWFL a large usable bandwidth of up to 80 nm, and it is expected that this will allow the SWFL to be used as a tunable laser source for high power applications to meet increasing demand.